Liquid Regionalism in Latin America: The Institutional and Trade Dynamics of the Latin American Integration Association - M. E. Morales-Fajardo (Vestnik MGIMO-Universiteta)
The Latin American Integration Association (LAIA) represents a commercial integration process that exemplifies the concept of liquid regionalism. Its defining characteristics include a lack of commitment and interest among member states, coupled with a pronounced pursuit of trade alternatives beyond regional boundaries. Rather than evolving into a robust common market, LAIA has primarily functioned as a zone of tariff preferences.This article aims to highlight the fragility of commercial integration within LAIA and to analyze the strong tendency toward extra-regional trade, which undermines the foundational principles of Latin American regionalism. The study provides a comprehensive examination of the historical context, evolution, and institutional framework of LAIA, with a particular focus on intra-regional trade dynamics and the Association's interactions with other regions and countries.The analysis concludes that LAIA epitomizes liquid regionalism in Latin America, a characterization stemming from the limited commitment of its member states, the institutional flexibility that defines its operations, and the prioritization of extra-regional trade at the expense of achieving its original objectives of economic integration and cooperation.Although LAIA was conceived within the framework of open regionalism in Latin America, it has not developed into a fully-fledged regional integration process. Instead, its focus has remained narrowly confined to facilitating trade exchanges. The intergovernmental regionalism model underpinning LAIA has failed to progress toward the establishment of a free trade area, contradicting the objectives outlined in the Treaty of Montevideo.